Come As You Are?: Democratizing Healthcare Through Black Church-Telehealth Initiatives - Parker, Meighan (Science and Technology Law Review, 2024)
Drawing from the phrase “come as you are,” which is frequently used in Black Churches to encourage and welcome people to church spaces for spiritual restoration and healing irrespective of their various social and economic dispositions, this Article aims to describe how telehealth partnerships with community organizations, such as Black Churches, can help democratize healthcare. In this project, I develop two models for Black Church-Telehealth Initiatives—a Telehealth Clinic on the Church’s campus and a Designated Telehealth Space with the requisite technology to facilitate telehealth encounters—to argue that Black Church-Telehealth Initiatives can help address certain social determinants of health, such as medical mistrust and the digital divide. The Telehealth Clinic would be a licensed medical facility where patients are assisted by medical personnel with seeing a remote physician via the appropriate technology (e.g., computer, video conference software, internet access, and medical devices to obtain certain biometric data). The Designated Telehealth Space, on the other hand, would be a room equipped with non-medical technology that is open to community members without access to the requisite technology for telehealth encounters. Black Churches are already important locations for promoting healthcare and can help further democratize healthcare via telehealth, if certain legal hurdles can be resolved. By exploring federal and state law and policy, I examine the legal barriers to telehealth expansion in general, and legal hurdles specific to these initiatives. This Article argues that federalism principles and widespread variation amongst state laws on physician licensure may make it more difficult to democratize healthcare via telehealth. Moreover, depending on the extent of the religious affiliation, Black Church-Telehealth Initiatives may fit into broader trends toward an increased alignment of healthcare institutions with religious organizations and their doctrines. Finally, legal and policy reforms are needed to address certain federal and state limitations on Medicare and Medicaid reimbursement, which may deter healthcare providers from collaborating with Black Churches to establish this Article’s initiatives. This makes the need for regulatory reform urgent. Indeed, as healthcare organizations partner with community organizations to expand access to telehealth, creative legal solutions will be required to subject those community organizations to important health laws and policies—including medical privacy and confidentiality laws—without stifling innovation and collaboration.